Hyaluronate lyase production by streptococcus pneumoniae isolated from patients and carriers - Ahmad Yusof @ Hanafi, Hanani; Mohd Desa, Mohd Nasir; Masri, Siti Norbaya; Osman, Malina; Jamal, Farida (Malaysian Society of Parasitology and Tropical Medicine, 2015)
Hyaluronate lyase produced by various microorganisms is capable of degrading hyaluronic acid in connective tissue and initiating spread of infection by opening an access for the pathogen into host tissues. The present study attempts to determine the distribution of hyaluronate lyase-producing Streptococcus pneumoniae among invasive, non-invasive and carriage isolates, and correlate it with the clinical sources, year of isolation, colonial morphology and their serotypes. A total of 100 isolates from various clinical samples were selected and screened for hyaluronate lyase production and presence of the encoding SpnHyl gene. All isolates possessed SpnHyl gene. Ninety-six isolates including 34 carriage isolates were positive for production of hyaluronate lyase. Four hyaluronate lyase-negative isolates were from blood (2 isolates) and sputum (2 isolates). No significant association was detected among hyaluronate lyase production and bacterial characteristics except for colonial morphology (p = 0.040). High percentages of hyaluronate lyase production in these isolates suggest their possible role as human pathogens.